2017
DOI: 10.1016/j.archoralbio.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β-induced gene product-h3 inhibits odontoblastic differentiation of dental pulp cells

Abstract: The present findings suggest that βig-h3 in DPCs may be involved in reparative dentin formation and that its expression is likely to negatively regulate this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We recently showed that DM promoted odontoblastic differentiation of HDPCs (Mizumachi et al, ; Serita et al, ). To examine the effects of TNF‐α on the odontoblastic differentiation of yHDPCs and sHDPCs, the cells were cultured in CM or DM with or without TNF‐α for 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that DM promoted odontoblastic differentiation of HDPCs (Mizumachi et al, ; Serita et al, ). To examine the effects of TNF‐α on the odontoblastic differentiation of yHDPCs and sHDPCs, the cells were cultured in CM or DM with or without TNF‐α for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that DM promoted odontoblastic differentiation of HDPCs (Mizumachi et al, 2017;Serita et al, 2017). To…”
Section: Effects Of Tnf-α On the Odontoblastic Differentiation Of Hdpcsmentioning
confidence: 95%
See 1 more Smart Citation
“…MTA has been reported to release calcium ions [39,40] and induce reparative dentin after the pulp exposure when it is applied as a direct pulp capping material [41][42][43][44]. We previously reported that CaCl 2 induces mineralization and odontoblastic differentiation of dental pulp cells [45]. As for the M2 macrophages, recent studies reported that M2 macrophages induce mineralization of the mesenchymal stem cells [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The same research group also showed that during experimental tooth movement of human premolars, βigh3 expression was significantly increased in the PDL [ 105 ]. Recently, βigh3 was also found to be expressed in rat pulp, where it could be associated with reparative dentinogenesis pointing to the potential therapeutic role of βigh3 in the pulpal repair process [ 106 ].…”
Section: Gla-containing Ecm Proteinsmentioning
confidence: 99%